Association between metabolic syndrome and lung function in middle-aged and elderly Chinese individuals. Issue 3 (June 2015) - Qin, Li; Yang, Zhen; Zhang, Weiwei; Gu, Hongxia; Lu, Shuai; Shi, Qun; Xing, Yin; Li, Xiaoyong; Li, Rui; Ning, Guang; Su, Qing
Highlights: 1842 participants aged 40 years or older have been studied. Lung function, evaluated by FVC and FEV1 was measured with standard spirometry. The subjects with MetS had lower FVC and FEV1 than non-MetS. FVC and FEV1 decreased according to the accumulation of the number of MetS components. Impaired lung function was associated with increased risk of MetS. Abstract: Subjects with metabolic syndrome (MetS) had lower FVC and FEV1 than non-MetS subjects and decreased gradually with the increasing number of MetS components. After adjusting for potential risk factors, the lowest quartile of FVC and FEV1 was associated with increased risk of MetS.